Peluang dan Tantangan Bisnis Online Pada Masa Pandemi COVID-19 - Nurul Rahmah Kusuma; Ana Fauziya Diyana (Jurnal Riset Bisnis dan Manajemen, 2021)
PSBB Policy or Large-Scale Social Restrictions policy is expected to suppress the spread of the virus and break the chain of spread in various regions in Indonesia. Although it has an impact on various sectors, it also creates new opportunities in the business system, which is called by online system. The study objective was to analyze the opportunities and challenges of online business during a pandemic. This study method used a descriptive qualitative approach with the object in the study was the MSME online business players who are domiciled in West Java. The data source in the study were taken from primary data sources by using interview techniques. The results of the study showed that the opportunities for economic trends during the pandemic can be seen from the progress of online businesses that may affect consumer behavior accompanied by challenges in the form of the public trust level in products.